2018
DOI: 10.3892/or.2018.6329
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone�D induces apoptosis and inhibits migration and invasion in human melanoma A375 cells

Abstract: The aim of the present study was to determine the effects of Licochalcone D (LD) on the apoptosis and migration and invasion in human melanoma A375 cells. Cell proliferation was determined by sulforhodamine B assay. Apoptosis was assessed by Hoechst 33258 and Annexin V-FITC/PI staining and JC-1 assay. Total intracellular reactive oxygen species (ROS) was examined by DCFH-DA. Wound healing and Transwell assays were used to detect migration and invasion of the cells. The activities of matrix metalloproteinase (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Cell migration was measured by wound‐healing assay to evaluate the inhibit migration effect of luteolin in vitro (Si et al, ). A375 and B16‐F10 cells were seeded in 60‐mm dishes at the density of 8 × 10 5 cells per dish to 90–100% confluence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell migration was measured by wound‐healing assay to evaluate the inhibit migration effect of luteolin in vitro (Si et al, ). A375 and B16‐F10 cells were seeded in 60‐mm dishes at the density of 8 × 10 5 cells per dish to 90–100% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Cell invasion was detected using Matrigel‐coated transwell chambers (8 μm pore size; Corning, USA) assay according to the manufacturer's instructions (Si et al, ). After pretreatment with or without (control) various concentrations (5, 10, and 20 μM) of luteolin for 24 hr, A375 and B16‐F10 cells were harvested and seeded into the upper chamber at the density of 4 × 10 4 cells per well in serum free medium.…”
Section: Methodsmentioning
confidence: 99%
“…Various pharmacological actions, including anti-oxidant, anti-biotic, anti-ulcer, and anti-carcinogenic effects, have been described for LCD [2]. Previous studies have demonstrated that LCD can induce cell apoptosis and suppress migration and invasion in skin cancer [3]. In addition, LCD can suppress the proliferation in oral cancer cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it attenuated migration, adhesion, and invasion of cancer cells accompanied with the downregulated protein expression of MMP-9 and nuclear translocation of nuclear factor-κB (NF-κB) [115]. Similar to licochalcone B, licochalcones C and D induced apoptosis by altering the expression of Bcl-2 family member genes and activating the caspase-mediated cell death signaling pathway [45,46]. Meanwhile, licochalcone D induced apoptosis through mitochondrial pathway and blocked cell migration and invasion into surrounding tissues by reducing the activity and expression of MMP-2 and MMP-9 [46].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Similar to licochalcone B, licochalcones C and D induced apoptosis by altering the expression of Bcl-2 family member genes and activating the caspase-mediated cell death signaling pathway [45,46]. Meanwhile, licochalcone D induced apoptosis through mitochondrial pathway and blocked cell migration and invasion into surrounding tissues by reducing the activity and expression of MMP-2 and MMP-9 [46]. In addition to increasing the expression of proteins (proapoptotic factors, caspase-3, and PARP), suppressing the constitutive NF-κB activation, and downregulating Bcl-2 and Bax, licochalcone E reduced tumor growth and metastasis through inhibiting tube formation of vascular endothelial cells [47][48][49].…”
Section: Anticancer Activitymentioning
confidence: 99%